2018
DOI: 10.3390/children5040050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Toothbrushing Education Via Video, Lecture and Pamphlet on the Dental Plaque Index of 12-Year-Old Children

Abstract: The aim of this study was to compare the effect of different modes of toothbrushing education (lecture, video and pamphlet) on the dental plaque index (PI) of adolescents. The cluster randomized intervention was performed on 128 participants aged 12 years, who were allocated into four groups based on the type of intervention. Group 1: no intervention; and groups 2, 3, 4: education via lecture, video, and pamphlet, respectively (n = 32). Their plaque index was measured at the baseline, 24 h and two months later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 9 publications
0
21
0
1
Order By: Relevance
“…Although printed materials could summarise content and be learnt repeatedly, the lack of practice details makes them less effective. 40 Videos hold advantages such as attractiveness, convenience, clarity of demonstration, superior cost-effectiveness and easy application, while lectures contain a variety of lively styles such as group interactions and scenario simulations, making them more popular. 41 42 Future studies should compare the effect of these measures.…”
Section: Discussionmentioning
confidence: 99%
“…Although printed materials could summarise content and be learnt repeatedly, the lack of practice details makes them less effective. 40 Videos hold advantages such as attractiveness, convenience, clarity of demonstration, superior cost-effectiveness and easy application, while lectures contain a variety of lively styles such as group interactions and scenario simulations, making them more popular. 41 42 Future studies should compare the effect of these measures.…”
Section: Discussionmentioning
confidence: 99%
“…All the participants were examined on a chair in a comfortable position with a head light, a plane mirror, and the Community Periodontal Index (CPI) probe, used for checking dental status. First, the Plaque Index (PLI) developed by Silness and Loe was utilized to record the plaque [18]. Then, the teeth were cleaned using a sterilized gauze and cotton to determine the DMFT index according to the procedures recommended by the WHO [17].…”
Section: Methodsmentioning
confidence: 99%
“…These results have important implications for the removal of dental plaque and habituation of appropriate brushing techniques. Several previous studies have investigated the effect of plaque removal by brushing, providing instructions about brushing methods, and also the association between brushing time and plaque removal [8][9][10][11]. Schluter et al investigated how to master the appropriate brushing methods by using leaflets or demonstrations, however their results showed the difficulties in mastering brushing methods [11].…”
Section: Plos Onementioning
confidence: 99%
“…The easiest self-care is through using a toothbrush and other dental materials. Previous studies have shown the effectiveness of removing plaque by brushing or brushing instructions [8][9][10][11][12]. Further, guidelines for periodontal disease treatment emphasize the importance of four processes in plaque control: motivation; self-care; the procedure of brushing; and professional care [1].…”
Section: Introductionmentioning
confidence: 99%